EFFICIENCY OF LARGE-SIZED MYSTUS KELETIUS (VALEN) IN EXTRACTING DISSOLVED OXYGEN FROM LOW PARTIAL PRESSURE - Santhanakumar, G; Job, S V; Vinojlal, S (Indian Journal of Fisheries, 2011)
Literature pertaining to partial pressure of dissolved oxygen (p02) temperature etc., are too scanty (Basu 1959, Beamish 1964, Fry 1947 and 1957, Job 1955 and 1957). In Tambaraparani river system, temperture ranges between 23 ± 1°C and 29 ± 1°C. The dissolved oxygen was found to be varying from 7.6 mg/1 to 2.5 mg/1 both in the surface and bottom (where depth is less than a meter), respectively.